1988
DOI: 10.1159/000110143
|View full text |Cite
|
Sign up to set email alerts
|

Case-Control Study of Associated Conditions at the Time of Death in Patients with Epilepsy

Abstract: Analysis of mortality data based on underlying cause of death in epileptic patients is of limited value in view of the low case-fatality ratio of epilepsy. Recently the National Center for Health Statistics has made available all conditions mentioned on each death certificate for the entire US population. Using a case-control study design, we have analyzed all the associated conditions at the time of death in patients with epilepsy for the year 1978. Association between epilepsy and the following conditions re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…The observation that S-FA decrease during methionine loading is reported earlier (6,20,27,31). The reduction in S-FA levels may be due to a temporarily reduced activity of the enzyme 5.10methylenetetrahydrofolate reductase (33).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The observation that S-FA decrease during methionine loading is reported earlier (6,20,27,31). The reduction in S-FA levels may be due to a temporarily reduced activity of the enzyme 5.10methylenetetrahydrofolate reductase (33).…”
Section: Discussionsupporting
confidence: 66%
“…Evidence from different studies has suggested that even a moderate elevation of p-tHcy is an independent risk factor for atherosclerotic disease (4,5). An increased incidence of ischemic heart disease and cerebrovascular disease have been observed in patients with epilepsy (6,7).…”
mentioning
confidence: 99%
“…Although much evidence shows that risk of mortality, including sudden unexpected death, is increased among people with epilepsy (15)(16)(17)(18)(19)(20), few data about seizurerelated injuries are available even though such injuries are far more common than fatal accidents. In the present study, injuries sustained during seizures were reported by one third of patients who had had at least one seizure in the previous year.…”
Section: Resultsmentioning
confidence: 99%
“…A case–control study design from the US mortality data study on epilepsy showed the association of mental retardation, cerebral palsy, cerebrovascular disease, myocardial ischemia, dementia, foreign body in pharynx and larynx, pneumonia, alcoholism and cirrhosis of liver with epilepsy at the time of death of epilepsy patients. [13]…”
Section: Sectionmentioning
confidence: 99%